Dynamic Behaviors and Analytical Solutions of the Damped (2+1)-Dimensional Nonlinear Schrödinger Equation - Yongyi Gu; Feng Ye; Baixin Chen; Najva Aminakbari (Advances in Mathematical Physics)
In this paper, abundant analytical solutions of the damped (2 + 1)-dimensional nonlinear Schrödinger equation are achieved by taking advantage of the extended systematic method. By considering various values of parameters, dynamic behaviors of bright, dark soliton, period wave, and kink solitary solutions are displayed with different amplitudes and directions in 3D graphs, lines, contour maps, and time evolution plots. Further analysis of the obtained results is studied to show the efficient effect of the parameters on the propagation and configuration of waves. In addition, computer simulations are considered to show the correlation between parameters and velocity. Our results indicate that the extended systematic method for solving differential equations is more convenient and yields richer solutions. The other mathematical physics equations that appear in nonlinear science can also be investigated by the concept of this study.